1977
DOI: 10.1073/pnas.74.9.3932
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of DNA-dependent RNA polymerase in a recA-independent pathway of genetic recombination in Escheria coli.

Abstract: Recombinant DNA molecules of phage X formed in Escherichia coli in the presence of chloramphenicol and/or rifampin can be assayed by their biological activity.recA -cells were found to be capable of forming recombinant A phage DNA in the presence of chloramphenicol. The relatively high recA-independent recombination observed in this system contrasts with the relatively low recA-independent recombination when recombinant phage particles rather than recombinant DNA are titrated. Formation of the recombinant DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The first evidence that transcription influences recombination comes from a study in which recombination between two λphages was shown to occur at transcribed sites independently of the HR protein RecA. 105 Importantly, these events required the activity of E. coli RNAP, as shown using the RNAP inhibitor rifampicin. Furthermore, the recombination sites were shown to be extended to new regions in rho termination mutants.…”
Section: Tar In Bacteriamentioning
confidence: 99%
“…The first evidence that transcription influences recombination comes from a study in which recombination between two λphages was shown to occur at transcribed sites independently of the HR protein RecA. 105 Importantly, these events required the activity of E. coli RNAP, as shown using the RNAP inhibitor rifampicin. Furthermore, the recombination sites were shown to be extended to new regions in rho termination mutants.…”
Section: Tar In Bacteriamentioning
confidence: 99%
“…The first evidence of TAR comes from l-phage studies showing that recombination occurs in transcribed DNA regions and depends on Escherichia coli RNA polymerase (RNAP) activity but not on RecA (Ikeda and Kobayashi 1977;Ikeda and Matsumoto 1979). Probably, the most influential reports on TAR were those showing the identification of the recombinant DNA (rDNA) sequence HOT1 as a hot spot of recombination in Saccharomyces cerevisiae (Keil and Roeder 1984), and the following demonstration that the ability of HOT1 to stimulate Rad52-dependent ectopic recombination of non-rDNA sequences depends on the RNAPI activity (Voelkel-Meiman et al 1987;Stewart and Roeder 1989).…”
Section: Transcription Stimulates Recombination From Bacteria To Humamentioning
confidence: 99%
“…An amber phage, K imm434 cI Daml5 FIam96B b538 red3, was added to one of the tubes in the presence of chloramphenicol, and another amber phage, K imm434 cI Sam7 RamS int6 red3, was added to the other tube under the same conditions (separate infection). After incubation with the drug, the cultures were mixed, and their DNAs were extracted as described previously by Ikeda and Kobayashi (9). Samples of the DNA preparation were packaged in vitro in a lysate of E. coli recA, NS428, and NS433.…”
Section: Resultsmentioning
confidence: 99%
“…Recombination of bacteriophage X is known to be mediated by functions of Escherichia coli genes, called rec, as well as viral genes, called red and int (6,7,18,20). We have previously shown that recA-independent homologous recombination of phage X takes place in the E. coli system, in which cells were jointly infected with phage X in the presence of chloramphenicol, a protein synthesis inhibitor, and intracellular X DNA was extracted and packaged in vitro to detect recombinant phage particles (9). The recombination takes place independently of Int and Red functions and is promoted by DNA-dependent RNA polymerase.…”
mentioning
confidence: 99%